INVESTIGATING ATTITUDE OF EFL PRE-UNIVERSITY LEARNERS TOWARDS AMERTISH ENGLISH - Eka Fitria Atmawati (Graduate Program, University of Islam Malang, 2020)
In learning and English, EFL leaners and teachers may concern to universe English but actual one the learn and teach specific one. Since there is no absolute boundary in how to learning and teaching English itself together with the growth of Englishes. This survey study makes out the differences of these British and American English and discusses the attitude of learners in term of how teachers of theirs varied in teaching English. The finding revealed that 86.08% of 627 respondents engage themselves in recognizing their knowledge in “Amertish English” and willingness to learn as the norm of English mastery. Further, 62.04-64.5% % of 323 respondents can easily recognize vocabulary items and spelling correctly compared to the use of grammar. 50.9% of respondents correctly differ the forms and 49.1% do incorrectly. Thus, a half of respondents face the language problem here. This means EFL half of learners here have been familiar with Englishes. 127 respondents met the English teachers with vary accents in teaching. Also, 108 respondents say quiet. This could really mean that as a main media of teaching and spreading English, teachers have been teaching English based on personal tendency.Keywords: Englishes, British and American English, EFL pre-university learners, Attitude.